Analisis Kualitas Air Sumur Gali terhadap Risiko Penyakit Kulit di Desa Bulu Bulu, Kabupaten Maros - Idris, Idris; Pannyiwi, Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2025)
Water quality is a crucial factor in maintaining public health, particularly in rural areas that still rely on traditional water sources such as dug wells. In Bulu Bulu Village, Maros Regency, most residents use dug well water for their daily needs, without knowing whether the water quality meets health standards. This study aims to analyze the physical, chemical, and microbiological quality of dug well water and identify the relationship between water quality and the incidence of skin diseases in the community. This study used an analytical survey method with a cross-sectional approach. The sample consisted of 15 randomly selected dug wells and 60 respondents who were active users of water from these wells. Laboratory tests were conducted to assess physical (color, odor, turbidity), chemical (pH, iron, nitrate), and microbiological (Escherichia coli) parameters. Data on skin diseases were collected through interviews, observations, and medical records from local health facilities. Data analysis used the Chi-square test to determine the relationship between water quality and the incidence of skin diseases. The results showed that most water samples contained E. coli contamination exceeding the threshold set by Minister of Health Regulation No. 32 of 2017. 63% of respondents experienced skin disorders, primarily contact dermatitis and fungal infections. A significant association was found between the microbiological quality of dug well water and the risk of skin disease (p < 0.05). This study emphasizes the need for regular water quality monitoring and public education regarding environmental sanitation and safe water source management.